Handbook of research on AI and knowledge engineering for real-time business intelligence - Hiran, Kamal Kant; Kannan, Hemachandran 1985-; Pise, Anil; Rabi, Justus (IGI Global, 2023)
"Nowadays, Artificial Intelligence is transforming most failed businesses into highly profitable businesses. The major aspect is historical data. With data and Artificial Intelligence and Knowledge Processing, we can find the current financial status of the organization, predict the future of the organization and if the loss has happened in the past consecutive years, we can know the reason behind the loss. With the help of knowledge processing, we can build decision support systems to make better decisions in business. AI-powered IoT creates intelligent technologies that imitate intelligent human behavior and aid in decision-making with little or no human interaction. AI can read, comprehend, and correlate data at breakneck speed, adding a new level of intelligence to blockchain-based business networks. The major research in Semantics, Artificial Intelligence, and Domain-specific applications are becoming more and more common in our daily lives, and the bulk of knowledge processing is becoming intellectual in a very wide sense. Even Artificial Intelligence with IoT and Blockchain found in a broad range of scenarios, from simple everyday tasks to more complex ones, such as transportation systems, business, finance, and even the medical field. Digital news, relationship networking, and advancements generated from expert decision handling are only a few examples of common usage. This research book seeks to give a broad understanding of the concepts, tools, and techniques that underpin data science, artificial intelligence with IoT and Blockchain and knowledge processing in business and industry"
Keywords: Business intelligence / Data processing; Artificial intelligence